Analisis SWOT terhadap Penerapan Marketing Mix 7P dalam Peningkatan Penjualan PT. Hanin Wisata Semesta - Syarifah, Tsaniyatas; Wiji Lailatul Maftukhah; Zamrodul Ardina (Institut Agama Islam Negeri Parepare, 2024)
This research aims to analyze the 7P marketing mix strategy at PT. Hanin Wisata Semesta using SWOT analysis. The SWOT analysis identifies the strengths, weaknesses, opportunities, and threats faced by Hanin Travel. Each variable within the 7P framework: Product, Price, Place, Promotion, People, Process, and Physical Evidence—is systematically examined to assess its role in influencing the company’s sales performance. The findings reveal that the 7P marketing mix strategy significantly impacts sales, either positively or negatively, depending on its implementation. The SWOT analysis further highlights critical areas requiring improvement to enhance the effectiveness of the marketing strategy and optimize sales growth. This study underscores the importance of strategic alignment and consistent evaluation in the application of the marketing mix to address market challenges and leverage potential opportunities. The recommendations derived from this research provide a practical roadmap for PT. Hanin Wisata Semesta to strengthen its market position and achieve sustained growth in a competitive industry.